Bronchial asthma: Advice for patients traveling to high altitude - Cogo, A.; Fiorenzano, G. (High Altitude Medicine & Biology, 2009)
This article examines the possibility of traveling to altitude for patients suffering from bronchial asthma. The mountain environment, the adaptations of the respiratory system to high altitude, the underlying pathophysiologies of asthma, and the recommendations for patients, according to altitude, are discussed. In summary, staying at low altitude has a significant beneficial effect for asthmatic patients, due to the reduction of airway inflammation and the lower response to bronchoconstrictor stimuli; for staying at moderate altitude, there is conflicting information and no clinical data; at high altitude, the environment seems beneficial for well-controlled asthmatics, but intense exercise and upper airway infections (frequent during trekking) can be additional risks and should be avoided. Further, in remote areas health facilities are often difficult to reach.